Numerical study on the stress and deformation behavior of buried PE pipeline exposed to stacking load - Pengcheng Li; Dong Lin; Ming Wen; Fei Wang; Chang Liu; Mingnan Sun; Jianguo Lu (PLoS ONE, 2025)
Oil and gas pipelines serve as critical infrastructure for ensuring energy resource supply and security. Stacking load, as one of the most widespread loads, frequently acts on the soil surface overlying buried polyethylene (PE) pipelines, influencing stress-strain dynamics and potential failure mechanisms. In this study, a numerical simulation model of pipeline-soil interaction for buried PE pipelines exposed to stacking load was established and verified. The variations in deformation and stress behavior were systematically analyzed. The results revealed that the maximum deformation of buried PE pipelines under stacking load occurred at the pipeline’s center, with upper and lower deformations, as well as diameter variations, diminishing progressively as the distance from the center increased. Furthermore, the difference between the upper and lower deformations was reduced as burial depth increased. Notably, the maximum deformation exhibited a direct proportionality with the stacking load, while both the deformation and its rate of reduction decreased with buried depth increased. Additionally, the peak stress within the buried PE pipeline emerged at the center of the load’s footprint, escalating in tandem with the increase in stacking load. Intriguingly, the stress response diverged between pipelines subjected to smaller and larger stacking loads, and the peak stress gradually attenuated as the pipeline’s diameter expanded. These findings highlight the importance of considering both stacking loads and buried depths in the design and installation for PE pipelines to safeguard structural integrity and extend operational lifespan.